A diabetes risk screening in Northern Cyprus: what we learned with FINDRISC. - Ozsoy, Serpil; Ozer, Emel (Progress in Nutrition, 2022)
Background: According to the data of IDF 2019, 463 million people with diabetes live in the world and it is predicted that this number will increase by 51% in the next 25 years and reach 700 million. T2 D is increasing due to industrialization, obesity, decreased physical activity and unhealthy lifestyle behaviors. Especially in individuals with a high risk of diabetes, physical activity intervention, development of healthy eating habits, obesity management and behavior change intervention reduce the development of diabetes by 58%.Objective: The aim of this research was to determine diabetes risk score of nurses with FINDRISC questionnaire. The FINDRISC questionnaire is a cost-effective and fast-applied scoring that does not require any intervention.Method: FINDRISC questionnaire was applied to the participants by face-to-face interview technique.Results: It was determined that as the age, body mass index and waist circumference values increased parallel with  the total score of FINDRISC.Conclusion: It is important to perform screening studies to identify high-risk groups for Type 2 diabetes in order to prevent or delay the development of Type 2 diabetes. It is thought that identifying high-risk individuals and preventing the development of diabetes by lifestyle changes can reduce both direct expenditures for medical care associated with the disease and indirect expenditures associated with loss of income and productivity.Key Words:Prediabetes, diabetes, diabetes risk, diabetes prevention, FINDRISC.